Green synthesis of silver oxide nanoparticle and its antimicrobial activity against organisms causing Dental plaques - COREENA FERNANDEZ; ANITHA THOMAS; M. SHAILAJA RAJ (International Journal of Pharma and Bio Sciences, 2016)
Biological synthesis of nanoparticles is gaining a lot of momentum as their synthesis is relatively easy, economically feasible, non-toxic and an extremely good alternative when compared to chemical and physical production techniques. During chemical synthesis, the chemicals used may be toxic and lead to non-eco-friendly by-products. This may be the reason why biosynthesis of nanoparticles via green route which does not employ toxic chemicals is gaining importance. Thus, the advancement of green synthesis of nanoparticles is progressing as a key branch of nanotechnology; where the use of biological entities like microorganisms, plant extract or plant biomass for the production of nanoparticles could be an alternative to chemical and physical methods in an eco-friendly manner. Silver nanoparticles were synthesized by green synthesis using Bacillus and E. coli cultures in the present study. The crude enzyme suspension from the cultures was treated with Silver Nitrate (AgNO3) solution. When the enzyme suspension was treated with silver nitrate, silver oxide nanoparticles were produced. The nanoparticles thus formed were confirmed spectrophotometrically at 420 nm which corresponds to the maximum absorbance of silver oxide nanoparticles. Further antimicrobial studies of these nanoparticles were also carried.